Bezpieczeństwo konstrukcji w świetle teorii kumulacji uszkodzeń - Eimer, C. (Engineering Transactions, 1969)
In this paper, the problem of the safety of structure has been presented with taking explicitly the time factor into account. Loads are considered as a stationary time-dependent stochastic process. The strength properties are considered as depending on the history of loading. The investigation has been based on the concept of damage and the hypothesis of cumulative damage which is known in the theory of material fatigue. This hypothesis has been generalized to the case of the arbitrary behaviour of loading. Two practical computing methods has been given: concerning the case in which the statistic data partain to maximum values of load in a fixed time period or the data which enable to calculate the distributions of loading probability.